2011
DOI: 10.1098/rsbl.2011.0480
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural flexibility and problem-solving in a tropical lizard

Abstract: The role of behavioural flexibility in responding to new or changing environmental challenges is a central theme in cognitive ecology. Studies of behavioural flexibility have focused mostly on mammals and birds because theory predicts that behavioural flexibility is favoured in species or clades that exploit a diversity of habitats or food sources and/or have complex social structure, attributes not associated with ectothermic vertebrates. Here, we present the results of a series of experiments designed to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 16 publications
4
89
0
4
Order By: Relevance
“…Regardless, we can at least parsimoniously align this species of squamate reptile to the broad taxa of animals that possess spatial memory during navigation, albeit the mechanisms underlying this navigation may differ significantly among various taxonomic groups. Finally, we also add to the growing body of evidence that exothermic taxa also possess some cognitive abilities which may be on par with mammals and birds [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless, we can at least parsimoniously align this species of squamate reptile to the broad taxa of animals that possess spatial memory during navigation, albeit the mechanisms underlying this navigation may differ significantly among various taxonomic groups. Finally, we also add to the growing body of evidence that exothermic taxa also possess some cognitive abilities which may be on par with mammals and birds [4].…”
Section: Discussionmentioning
confidence: 99%
“…In many animals, spatial memory has been explicitly tested for and verified. However, spatial memory capabilities in squamate reptiles have been debated [1 -3], even though recent evidence has shown that reptiles may possess other typically higher cognitive processing [4]. Thus, in squamate reptiles, the existence of spatial memory has been contentious, probably owing to the paucity of studies explicitly testing it.…”
Section: Introductionmentioning
confidence: 99%
“…Our social demonstration experiments were modified versions of an instrumental and association-based foraging task previously used with lizards [7,10]. We first accustomed all lizards (n ¼ 48) to eating mealworms (Tenebrio molitor) from an open dish.…”
Section: (A) Social Demonstration Experimentsmentioning
confidence: 99%
“…Lizards are likely to be good candidates for testing social learning because they show behavioural flexibility and rapid learning [7][8][9]. We tested for age-related social learning in a non-group-living lizard (Eulamprus quoyii) known for relatively rapid spatial learning ability [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The discussion of evolution through natural selection covers well-traveled terrain, such as the influence that genes have on behavior, but also highlights how behavior can affect genes. Classic (Skinner 1984(Skinner , 1986) and contemporary (Ginsburg and Jablonka 2010;Leal and Powell 2012) theories relating the impact that behavior may have on survival are presented as compliments to established evolutionary theories (Dawkins 1976;Gould 1989Gould , 2002.…”
Section: Chapter Highlightsmentioning
confidence: 99%